Menakar Paradigma Penanggulangan Bencana Melalui Analisis Undang-Undang No. 24 Tahun 2007 Tentang Penanggulangan Bencana - Setyorini, Fitri Adi (Journal of Social Politics and Governance (JSPG), 2023)
This study discusses the paradigm used by the Indonesian government in making domestic disaster management policies through analysis of Law No. 24 of 2007. Institutions in the National Disaster Management Agency (BNPB) have developed policies related to the development of issues of change and developments in domestic and international politics. This writing aims to analyze the paradigm used by the Indonesian government in making policies on domestic disaster management through analysis of Law No. 24 of 2007. The author uses the content analysis method in analyzing these laws. Analysis was carried out on five indicators; actors, authority, budget, governance, and output that represent three paradigms; realism, liberalism and constructivism. Based on the results of the analysis, the Disaster Management Law is highly dependent on the paradigm of realism.